Constitution, objects, and proceedings of the Financial Reform Association . ; (publ. by the Association, 1858)
The title of the second article inside reads: The Hudson's Bay Company, and the late government. In pamphlet volume with covertitle: Tracts of the Financial Reform Association : second series ...